Human haematopoietic stem cell development: from the embryo to the dish - Ivanovs, Andrejs; Rybtsov, Stanislav; Ng, Elizabeth S; Stanley, Edouard G; Elefanty, Andrew G; Medvinsky, Alexander (Development (Cambridge), 2017)
Haematopoietic stem cells (HSCs) emerge during embryogenesis and give rise to the adult haematopoietic system. Understanding how early haematopoietic development occurs is of fundamental importance for basic biology and medical sciences, but our knowledge is still limited compared with what we know of adult HSCs and their microenvironment. This is particularly true for human haematopoiesis, and is reflected in our current inability to recapitulate the development of HSCs from pluripotent stem cells In this Review, we discuss what is known of human haematopoietic development: the anatomical sites at which it occurs, the different temporal waves of haematopoiesis, the emergence of the first HSCs and the signalling landscape of the haematopoietic niche. We also discuss the extent to which differentiation of human pluripotent stem cells recapitulates bona fide human developmental haematopoiesis, and outline some future directions in the field.